Structural, magnetic and dielectric studies on half-doped Nd0.5Ba0.5CoO3 perovskite - Kumar D.; Jena P.; Singh A.K. (My University, 2025)
We have investigated in detail the structural, magnetic, and dielectric properties of half-doped Nd0.5Ba0.5CoO3 perovskite cobaltite synthesized by the auto-combustion method. The Rietveld structure refinement from X-ray diffraction pattern reveals that a polycrystalline sample of Nd0.5Ba0.5CoO3 crystallizes into an orthorhombically distorted crystal structure with space group Pmmm along with a minor distorted tetragonal phase with P4/mmm space group. The temperature dependence of magnetization measurements show paramagnetic to ferromagnetic phase transition at Curie temperature TC around 147 K for H = 200 Oe. The value of TC strongly depends on the applied magnetic bias field, and TC decreases with an increasing magnetic field. The polycrystalline sample of Nd0.5Ba0.5CoO3 cobaltite exhibits Griffiths’ phase in the temperature range 147 K ≤ T ≤ 235 K for H = 200 Oe. Investigation of the isothermal magnetic field measurements on Nd0.5Ba0.5CoO3 reveals that it exhibit antiferromagnetic, ferromagnetic and paramagnetic behaviors, at T = 2 K, 100 K and 150 K, respectively. The negative slope of the isothermal Arrott's plots (i.e., H/M versus M2) in the low magnetic field region suggests a first-order magnetic phase transition while the positive slope in high magnetic field region reveals a second-order magnetic transition. The dielectric constant and electrical resistivity of the synthesized Nd0.5Ba0.5CoO3 cobaltite material decrease with increasing temperature as well as frequency. Bulk Nd0.5Ba0.5CoO3 cobaltite shows insulator/semiconductor to metal transition at 76 °C. © 2020 Elsevier B.V.